The Upward Mobility Potential in U.S. Intercollegiate Athletics: A Critical Examination of NCAA Division I College Baseball Players’ Hometown Demographics - Kirsten Hextrum; Jeremy Kim (Journal of Intercollegiate Sport, 2023)
American meritocratic ideology positions sports as level playing fields in which individuals, regardless of their background, can ascend with the right combination of ability and effort. Yet few studies challenge the sport-meritocracy ideology by empirically examining the socioeconomic backgrounds of college athletes (Allison et al., 2018). Studies of youth sport participation show that community-level income shapes athletic opportunities suggesting class is a strong barrier to physical activity (NWLC, 2015; Sabo & Veliz, 2008; Tompsett & Knoester, 2022). Class inequalities are exacerbated in sports with robust privatized youth systems like baseball (Klein et al., 2020; Post et al., 2022). Utilizing a unique quantitative dataset of NCAA Division I college baseball players (n = 19,987), we consider the extent to which a community’s socioeconomic levels and racial demographics shape the chances of someone becoming a college baseball player. We compare college baseball players’ hometown income levels and racial demographics to their home state and to U.S. averages. We also consider differences across competitive divisions (i.e., Non-Power 5 vs. Power 5). Findings show that college baseball players—regardless of conference affiliation—commonly come from affluent, nonminority cities, with high education and income levels, indicating that socioeconomic status is a significant predictor of college athletic participation.